Controlling Strategies of Citrus to Increase The Yield in The Country: A step Towards The Fight Against COVID-19. Issue 1 (November 2021) - Abbas, Ghulam; Al-Taey, Duraid K.A.; Al-Azawi, Saad S.M.; Mehdizadeh, Mohammad; Qureshi, Razia A. M.; Jasman, Ammar K; Slomy, Ali K; Khan, Mumtaz A.; Jabbar, Makhdoom Abdul; Iqbal, Asif; Arshad, Maria; Rehman, Jalees Ur; et al.
Abstract: Citrus (oranges, lemon, mandarin, limes and tangarines) has significant nutritional value in human foods. It is rich source of vitamin C, sugar, organic acids, amino acids, minerals like Ca, Mg and various other phytochemicals (flavonoids, hesperidin etc) compounds that are responsible for good health. Citrus is growing in more than one forty countries of the world including Pakistan, Brazil, China, Mexico, USA, Spain and India.Viral infection and inflammation triggers the production of oxygen free radicals and these radicals severely damage the cells, however hesperidin and vitamin C is reported to counteract these damages. Intake of plentiful citrus fruits is one of amongst the many possible approaches to prevent from COVID-19 role of nutrition. Citrus fruit are very rich in important substances with a potential beneficial for health such as modulating the immunity and in protecting cells from oxidative stress related with infection. Flavonoids and hesperidin two major key compound found in citrus have affinity to treat Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Hesperidin has a low binding energy, both with the coronavirus "spike" protein, and with the fundamental protease that alters the primary proteins of the virus (pp1a and ppa1b) into the complex liable for viral replication hence these compounds could work as an antiviral function. Pakistan is amongst top ten citrus producers in the world. Citrus is one of the best commercial fruits of Pakistan cultivated on a large area, however, in Pakistan yield of citrus has been affected due to attack of insects and pathogens (nematode, fungal, bacterial and viral) which causes heavy losses both in quality and quantity. The purpose of this article is to focusing on the controlling the pathogens of citrus to boost citrus production in country as these beneficial plants are well known for its essential vitamin and flavonoid contents to control COVID-19.